Atlas of Functional Anatomy for Regional Anesthesia and Pain Medicine : Human Structure, Ultrastructure and 3D Reconstruction Images - Reina, Miguel Angel; De Andrés, José Antonio; Hadzic, Admir; Prats-Galino, Alberto; Sala-Blanch, Xavier; van Zundert, André A.J (Springer International Publishing : Imprint: Springer, 2015)
This is the first atlas to depict in high-resolution images the fine structure of the spinal canal, the nervous plexuses, and the peripheral nerves in relation to clinical practice. The Atlas of Functional Anatomy for Regional Anesthesia and Pain Medicine contains more than 1500 images of unsurpassed quality, most of which have never been published, including scanning electron microscopy images of neuronal ultrastructures, macroscopic sectional anatomy, and three-dimensional images reconstructed from patient imaging studies. Each chapter begins with a short introduction on the covered subject but then allows the images to embody the rest of the work; detailed text accompanies figures to guide readers through anatomy, providing evidence-based, clinically relevant information. Beyond clinically relevant anatomy, the book features regional anesthesia equipment (needles, catheters, surgical gloves) and overview of some cutting edge research instruments  (e.g. scanning electron microscopy and transmission electron microscopy).                 Of interest to regional anesthesiologists, interventional pain physicians, and surgeons, this compendium is meant to complement texts that do not have this type of graphic material in the subjects of regional anesthesia, interventional pain management, and surgical techniques of the spine or peripheral nerves.